2021
DOI: 10.18632/oncotarget.28060
|View full text |Cite
|
Sign up to set email alerts
|

Safety and initial efficacy of ablative radioembolization for the treatment of unresectable intrahepatic cholangiocarcinoma

Abstract: Purpose: To investigate safety, response, and survival after ablative glass microsphere 90 Y radioembolization for unresectable intrahepatic cholangiocarcinoma. Materials and Methods: A retrospective review of 37 radioembolizations in 28 patients treated with single compartment dose of ≥190 Gy encompassing >75% of the largest tumor was performed. Tumors were assessed for stage, morphology, and arterial supply. Response per Modified Response Evaluation Criteria in Solid Tumors (mRECIST), freedom from progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 24 publications
(28 reference statements)
1
14
0
Order By: Relevance
“…In 2010, Saxena et al [ 60 ] reported that patients with mass-forming peripheral ICCs have a longer median survival duration than do patients with infiltrative lesions (18.3 months vs. 4.5 months). Similar results were also reported in a recent study by Paz-Fumagalli et al [ 26 ], indicating that patients with mass-forming tumors had a longer survival ( p = 0.002). Furthermore, as shown in several studies included in the present review, patient survival varies according to whether SIRT was used as a first-line treatment (for treatment-naïve ICC patients), for chemotherapy-refractory disease, or after the failure of other therapies [ 23 , 28 , 31 , 35 , 51 ].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In 2010, Saxena et al [ 60 ] reported that patients with mass-forming peripheral ICCs have a longer median survival duration than do patients with infiltrative lesions (18.3 months vs. 4.5 months). Similar results were also reported in a recent study by Paz-Fumagalli et al [ 26 ], indicating that patients with mass-forming tumors had a longer survival ( p = 0.002). Furthermore, as shown in several studies included in the present review, patient survival varies according to whether SIRT was used as a first-line treatment (for treatment-naïve ICC patients), for chemotherapy-refractory disease, or after the failure of other therapies [ 23 , 28 , 31 , 35 , 51 ].…”
Section: Discussionsupporting
confidence: 90%
“…After implementing our exclusion criteria, 47 papers were eligible for data extraction. Of the final 47 included papers, 40 were journal articles [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ] ( Table 1 ), and seven were conference abstracts [ 62 , 63 , 64 , 65 , 66 , 67 , 68 ] ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients have no special clinical symptoms in the early stage of the disease. With the prolongation of the disease time, the patients will have clinical symptoms such as fever, abdominal pain, fatigue, jaundice, and loss of appetite [ 1 ]. At present, cholangiocarcinoma is mainly treated by nutritional support, surgery, radiotherapy and chemotherapy, and interventional therapy [ 2 ].…”
Section: Introductionmentioning
confidence: 99%